Energy transition for the low-carbon pulp and paper industry in China. (October 2020) - Man, Yi; Li, Jigeng; Hong, Mengna; Han, Yulin
Abstract: Pulp and paper industry is one of the eight critical industries for controlling carbon emissions in China. As the paper productions increase, the pulp and paper industry may fail in achieving the emission reduction target due to the rapid growth of greenhouse gas emissions. The study uses life cycle assessment to evaluate the greenhouse gas emissions of China's papermaking industry chain in order to propose emission reduction targets and find ways to achieve the emission reduction targets for China's papermaking industry. Considering the net carbon absorption of plant raw materials and the extensive paper industrial chain, this study obtained that the greenhouse gas emission of major paper types under corresponding pathways ranges from 1.96 t CO2 eq/t paper to 6.55 t CO2 eq/t paper. Plant carbon sink can reduce greenhouse gas emissions by 14.3%–42.9% under virgin fiber-based pathways. This study found that the greenhouse gas emissions caused by terminal products of 814 papermaking enterprises counted in China were 282.23 Mt CO2 eq in 2015, accounting for 10.23% of the total greenhouse gas emissions of manufacturing industries and construction. To achieve the emission reduction target by 2050, emissions of the pulp and paper industry in China have been investigated from the perspective of three ideal energy structures. The research findings show that the emission reduction target of Intended Nationally Determined Contribution will be achieved in 30 years if the energy structure of the pulp and paper industry is adjusted only based on the optimal 450 scenario. In terms of other energy structures, the pulp and paper industry should assume afforestation areas ranged from 5900 km 2 to 223, 000 km 2 at least to make up for the greenhouse gas emissions beyond allowance, which accounts for 0.85%–32.16% of the existing areas of plantation forestry in China. Highlights: Statistics in this work reveal the problem of excess capacity in China's pulp and paper industry. GHG emission of paper products in different pathways range from 1.95 to 6.52 t CO2 eq/t paper. Energy supply mode transition is conductive to green development of pulp and paper industry. Pulp and paper enterprises should assume afforestation areas to achieve emission reduction targets.